Effect of using different intensities in resistance training for muscle hypertrophy gains - a narrative review - Callegari, I. O. M.; Santarem, P. S. M.; Arrivabene, T. T.; Oliveira, A. G. (Strength and Conditioning Journal, 2024)
Resistance training or strength training has become one of the most popular forms of exercise, because it is the only method capable of improving physical fitness and increasing muscle mass simultaneously. Among the variables of training, the relationship between intensity and volume has been extensively addressed to enhance exercise-induced muscular hypertrophy. For many, mechanical stress is seen as a factor of greater relevance and, because high loads promote greater mechanical tension and high intensities are traditionally used to increase muscle mass. However, evidence has shown greater safety and similar results through training based on lower intensities and increased training volume. Thus, this narrative review aimed to search the current literature for evidence on using different training loads to promote muscle hypertrophy. An extensive nonsystematic literature review was conducted in the PubMed, Google Scholar and Scielo databases. It was possible to conclude that the use of high and low intensity promotes similar results in muscle hypertrophy in all groups, leading to the belief that there is greater safety and adherence to the use of lower intensities compared with close effort to concentric failure.